1997
DOI: 10.1017/s0021859697004267
|View full text |Cite
|
Sign up to set email alerts
|

Urea as a nitrogen fertilizer for cereals

Abstract: Twenty-six experiments were carried out in England and Wales from 1983 to 1985 to compare urea and ammonium nitrate (AN) as N top-dressing for cereals over the range 100-300 kg\ha N. Most of the experiments were sited on chalky or other soils of pH 7n0 where the greatest differences in effectiveness were expected.The results showed that while relative N offtake in grain was 2n5 % greater from AN, there was no difference in grain yield. Splitting the main N application increased N offtake from urea but not from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…Aliu et al (2009) in their field experiments found the highest value of LAI for maize inbred L7 (3.9) in 1 st year and 4.0 in 2 nd year, whereas the lowest LAI was noted for maize inbred L10 (2.52) in 1 st year, while in 2 nd year the lowest LAI (2.6) was obtained for inbred L8. Amanullah et al (2007) Lloyd et al (1997) noted that increase in yield with N application at all sites. But at three sites (B6, B8 and C7), yield was greater with ammonium nitrate, while at two sites (B9 and C13) yield was greater with application of urea.…”
Section: Year Effectsmentioning
confidence: 90%
“…Aliu et al (2009) in their field experiments found the highest value of LAI for maize inbred L7 (3.9) in 1 st year and 4.0 in 2 nd year, whereas the lowest LAI was noted for maize inbred L10 (2.52) in 1 st year, while in 2 nd year the lowest LAI (2.6) was obtained for inbred L8. Amanullah et al (2007) Lloyd et al (1997) noted that increase in yield with N application at all sites. But at three sites (B6, B8 and C7), yield was greater with ammonium nitrate, while at two sites (B9 and C13) yield was greater with application of urea.…”
Section: Year Effectsmentioning
confidence: 90%
“…The higher cost of AS was due to the presence of sulfur (24%) and also having more transportation charges than urea. Lloyd et al (1997) reported that urea was a less expensive form of N fertilizer than ammonium nitrate. However, urea is considered less effective than other N fertilizers because of N loss by ammonia volatilization, especially when used on soils of high pH or low CEC (Terman, 1979).…”
Section: Methodsmentioning
confidence: 99%
“…According to Chien et al AS is the best N-fertilizer source which contains frees sulfur and had many potential agronomic and environmental benefits over urea and ammonium nitrate [14]. In Lloyd et al reported that urea (£100 per ton) is a less expensive form of N fertilizer than ammonium nitrate (£130 per ton) [15]. However, urea has been considered to be less effective than other N fertilizers, due to N loss by ammonia volatilization, especially when used on soils of high pH or low CEC [16].…”
Section: Days To Physiological Maturitymentioning
confidence: 99%
“…According to Swift et al and Amanullah et al urea gave 3% less total DM production than ammonium nitrate and produced on average 7 % less DM in the spring, and 12% less in autumn [31,32]. However, urea could be a suitable alternative to ammonium nitrate, and when used in spring must be about 20 % cheaper per kg N. In Lloyd et al found that grain yield was unaffected by the type of N-fertilizer N, but grain N concentration was usually less from urea than ammonium nitrate [15]. The early maturity and higher SOC in maize due to AS application could be due to presence of free S in it that helped the maize plants to achieve early PM and increased SOC.…”
Section: Seed Weightmentioning
confidence: 99%